El Decameron de Pasolini: manipulación “de autor” - Cuevas, Miguel Ángel (Cuadernos de Filología Italiana, 2011)
Boccaccio’s prose is translated as “cinema of poetry”; Pasolini transforms in detail in “hallucinatory immediacy,” the logical and psychological life, movement boccacciano fictional character. The tunes iconographic pose as many keys to the insight of the process, which ends in the construction of the “disciple of Giotto”, a sort of fictional self.
Keywords: Imagery; Poetic film; Author’s manipulation; Autobiographism